2022
DOI: 10.1016/j.brs.2022.01.008
|View full text |Cite
|
Sign up to set email alerts
|

How structural and functional MRI can inform dual-site tACS parameters: A case study in a clinical population and its pragmatic implications

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 102 publications
(132 reference statements)
0
20
0
Order By: Relevance
“…Stimulation model: A model that includes technical properties of the stimulator and its mechanism of action to predict the optimized protocol based on the inputs from the stimulation model. activity/connectivity [21]. For example, Stanford neuromodulation therapy (SNT) paradigm provided by Cole et al [22], reported that individualized functional-connectivity-guided targeting using resting-state fMRI in a high dose intermittent theta burst stimulation (iTBS) trial was more effective than sham stimulation for treatment resistant depression [22].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation model: A model that includes technical properties of the stimulator and its mechanism of action to predict the optimized protocol based on the inputs from the stimulation model. activity/connectivity [21]. For example, Stanford neuromodulation therapy (SNT) paradigm provided by Cole et al [22], reported that individualized functional-connectivity-guided targeting using resting-state fMRI in a high dose intermittent theta burst stimulation (iTBS) trial was more effective than sham stimulation for treatment resistant depression [22].…”
Section: Introductionmentioning
confidence: 99%
“…Neither patients nor caregivers believed that a technique like tDCS can completely replace psychotherapy or 'talking'. In fact, 'talking', personal contact and the role of the caregiver are regarded as the most important aspects of psychotherapy 44 that positively contribute to willingness to participate in research (especially among traumatized patients 55 ), treatment acceptability 53,56 , therapeutic effectivity, and self-efficacy in managing symptoms 43,53,[56][57][58][59] . Accordingly, treatments for PTSD and anxiety without these interpersonal aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, disrupted functioning of other areas in the prefrontal cortex (such as dorsolateral and ventrolateral parts) leads to exaggerated expectations of danger and avoidance behavior. Impaired activation of these areas has been associated with impaired emotion regulation and impaired executive control functions such as attention deficits and impulsivity 44,56,57 . Hence, targeting activity in dorsolateral and ventrolateral prefrontal cortex regions may restore impairments in regulatory functions like emotion regulation and executive control and thereby support adaptive coping with stress.…”
Section: When Does It Go Wrong?mentioning
confidence: 99%
See 2 more Smart Citations